Evaluasi Program Pencetakan Sawah Baru (Studi Kasus di Kecamatan Kota Jantho) - M Syam Reza Purba; Suyanti Kasimin; Otto Nur Abdullah (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
While in the 2016, Aceh Besar government had printed 512 acres new paddy field successfully that scattered in several villages. The new paddy field that had been printed successfully had been realized by 100% as the planned target, but several villages didn’t reach the planting area target. It means there still hurdles in the several villages that hindering so that new paddy field can’t be used as the planting area, especially Jantho district. Therefore, it’s necessary to have an evaluation of the success of a new paddy field printing program. The purpose of this research is to analyze and describe the evaluation of a new paddy field printing program based on CIPP (Context, Input, Process and Product) evaluation model. The data used in this research are primary and secondary data. Researchers used descriptive analysis based on CIPP model program. The result of this research show that the paddy field printing program that had been done in Kota Jantho district still has several ineffective aspects from each CIPP component based on descriptive analyzing and CIPP model program evaluation. The ineffective aspects are 1) Agricultural conseling officers (PPL) availability, 2) New rice field printing program recipients (farmers) availability, 3) Aceh Besar government’s supports, 4) The Hurdles faced by the farmers in utilizing the new rice field printed and 5) The rice’s harvest growth in Kota Jantho district.